Phraseological uses in the text of detective prose - Gabdrakhman, Т.С. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The article explores phraseological uses in the language of fiction works of the detective genre. The object of the study is the work of Kemel Tokayev, who wrote the first works of this genre in Kazakh literature, including the works "The soldier went to war", "Shot at night", "Flood". The works of the writer, written in the genre of adventure prose, occupy a large place in Kazakh literature. The purpose of the article is to identify the linguistic and stylistic features of phraseological units of the Kazakh detective genre. In this regard, the tasks of analyzing the use, function, and style of stable expressions were set. It is noted that in the works taken on the object of research, the potential of phraseological units is widely used: both national phraseological units and literary phraseological units, the original use of the writer are freely used. The article examines how phraseological units in a detective novel influence the behavior of the characters, the creation of an atmosphere of tension and the development of the plot. The results of the study allow us to better understand how phraseological units interact with other linguistic means to achieve the author's goal in detective literature.